SOCIAL PEDAGOGICAL ASSISTANCE FOR STUDENTS WHO EXPERIENCE BULLYING SITUATIONS AT SCHOOL - Klanienė, Ilona; Bražinskienė-Gružauskė, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The frequency of bullying and the consequences for the child's development encourage targeted social pedagogical assistance in Lithuanian schools. The article reveals the opportunities of social pedagogical assistance at school for students who have experienced bullying by peers. The results of the qualitative research (partially structured interviews with school leaders, social pedagogues, and class teachers) are presented. The analysis of the research results has revealed that the following social pedagogical support measures are applied at school: the provision of emotional support, consultations, social skills classes, work with parents, individual conversations and etc.. The main difficulties identified by the informants in assisting students are the lack of parental cooperation, the passivity of teachers and a lack of staff competencies to deal with bullying situations. By increasing the possibilities of social pedagogical assistance at school, the informants offer to increase parental responsibility, improve pedagogues‘ competencies, cooperate with assistance organisations.